Pengaruh Revisi Anggaran, Partisipasi Anggaran dan Tingkat Kesulitan Terhadap Pencapaian Anggaran yang Efektif pada Hotel Berbintang di Kota Denpasar. - Aprianti Jw, Km Sri; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This study aims to obtain empirical evidence of the effect of budget revisions, budget participation, and the level of difficulty of budget targets on budget effectiveness at star hotels in Denpasar City. In this study the dependent variable is Budget Effectiveness, while the independent variables in this study are Budget Revision, Budget Participation and Difficulty Level of Budget Targets. The method used is incidental sampling, namely conducting a survey by distributing questionnaires to respondents using (google form).  The method of determining the sample uses the incidental sampling approach. The data analysis technique uses multiple linear regression. The results show that the Budget Revision has a positive and insignificant effect on Budget Effectiveness, Budget Participation has a positive and significant effect on Budget Effectiveness, and the Difficulty Level of Budget Targets has a positive and significant effect on Budget Effectiveness.